Synthesis Of Polyvinyl Alcohol Multiwalled Carbon Nanotubes Composites For Malachite Green Adsorption - Chong, Yian Sing (Universiti Sains Malaysia, 2022)
Synthesic dyes are widely applied in the industries, typically textile industries, resulting the growth of water pollution. One of the common dyes used is malachite green (MG). This project aimed to generate polyvinyl alcohol/ multiwalled carbon nanotubes (PVA/MWCNTs) nanocomposites using polyvinyl alcohol (PVA) as the support for the MG adsorption from aqueous solution. Phase inversion was the synthesis technique employed to prepare the pure PVA beads as well as PVA/MWCNTs beads. The effects of several parameters, such as the initial dye concentration, adsorbent dosage, and contact time, were studied. The optimum contact time was 2880 minutes. The findings revealed that there are several ways to increase the removal efficiency, firstly, by lowering the starting dye concentration and secondly, by increasing contact time and lastly, by increasing the adsorbent dosage. At an initial dye concentration of 5 mg/L and PVA/MWCNTs adsorbent dosage of 2500 mg, the removal efficiency obtained was 100 % which is significantly higher as compared to pure PVA adsorbent, which was only 42.26 %. The adsorbent's adsorption capacity decreased as the initial dye concentration decreased, resulting from the higher driving force of the concentration gradient. The Langmuir isotherm model and the pseudo-second order kinetic model provided the best fits for the experiment data in terms of adsorption isotherm and kinetics. The uptake of MG dye was referred to as monolayer adsorption, with chemisorption as the rate-determining step. The monolayer maximum adsorption capacity of MG dye attained was 2.28 mg/g for PVA/MWCNTs composites and 0.02 mg/g for PVA adsorbents. In light of these findings, PVA/MWCNT nanocomposites are a promising potential adsorbent for the treatment of MG dyes in wastewater.